OPEN OUTCRY AND ELECTRONIC FINANCIAL TRADING SYSTEMS (A Comparison Study) - Khristianto, Wheny (JURNAL PERSPEKTIF BISNIS, 2013)
The impact of the Internet in the financial and accounting fields has created vast electronic marketplaces for the purchase and sale of stock, bonds, and other financial products. With rapid technological advantages, growing trading volume, and an increased demand for a more efficient trading environment, the majority of futures exchanges have introduced various forms of electronic trading. Despite this directive, a few futures exchanges still use open outcry trading. On the other sides, The impact of electronic trading in the future exchange is very significant. This article compares open outcry and electronic trading in the ability to create liquidity, the ability to reduce direct cost, and the ability to make global links.Key words: Internet, open outcry trading, electronic financial trading